Compressive behaviour of tin slag polymer concrete confined with fibre reinforced polymer composites exposed to tropical weathering and aggressive conditions - S. S., Amirnuddin; Muhamad Soffi, Manda; Shukur, Abu Hassan; Mat Uzir, Wahit; Mohd Ruzaimi, Mat Rejab; Joseph Selvi, Binoj Selvi; Ahmad Ilyas, Rushdan (Elsevier Ltd, 2023)
Tin slag, which is high in silica content, is a by-product of the smelting process. The outcome is anticipated to improve the compressive strength of polymer concrete composites. In light of this, the purpose of this research is to examine the durability of polymer concrete utilising tin slag as its fine aggregates and to determine the potential use of tin slag in place of other materials to create either primary or secondary type polymer concrete-based structures. Tin slag polymer concrete (TSPC) was confined to FRP composites and subjected to tropical climate and exposure to an aggressive environment. The test results were analysed and discussed in relation to compressive strength and modulus resulting from tropical climate and exposure to an aggressive environment. The results revealed that confined samples which had been externally reinforced with carbon fibre/epoxy (CFRP) and glass fibre/epoxy (GFRP) composites showed a significant enhancement in terms of strength and modulus compared to unconfined sample groups. The compressive modulus for Lab exposure increased about 7 % for GFRP_LAB, 27 % for CFRP_LAB compared to the U_LAB sample. The number of layers wrap does not significantly affect the material. Meanwhile, the decrease in modulus and compressive strength of the samples exposed to tropical climate indicated the effects of moisture on the mechanical behaviour of TSPC. There were decreased about –0.516% for U_OUT, –8.42% (GFRP_OUT) and –8.45% (CFRP_OUT).